Pubertal FGF21 deficit is central in the metabolic pathophysiology of an ovine model of polycystic ovary syndrome. (5th April 2021) - Siemienowicz, Katarzyna J.; Furmanska, Klaudia; Filis, Panagiotis; Talia, Chiara; Thomas, Jennifer; Fowler, Paul A.; Rae, Mick T.; Duncan, W. Colin
Abstract: Polycystic ovary syndrome (PCOS), affecting over 10% of women, is associated with insulin resistance, obesity, dyslipidaemia, fatty liver and adipose tissue dysfunction. Its pathogenesis is poorly understood and consequently treatment remains suboptimal. Prenatally androgenized (PA) sheep, a clinically realistic model of PCOS, recapitulate the metabolic problems associated with PCOS. Fibroblast Growth Factor 21 (FGF21) is a metabolic hormone regulating lipid homeostasis, insulin sensitivity, energy balance and adipose tissue function. We therefore investigated the role of FGF21 in the metabolic phenotype of PA sheep. In adolescence PA sheep had decreased hepatic expression and circulating concentrations of FGF21. Adolescent PA sheep show decreased FGF21 signalling in subcutaneous adipose tissue, increased hepatic triglyceride content, trend towards reduced fatty acid oxidation capacity and increased hepatic expression of inflammatory markers. These data parallel studies on FGF21 deficiency, suggesting that FGF21 therapy during adolescence may represent a treatment strategy to mitigate metabolic problems associated with PCOS. Highlights: Prenatal androgenization of female sheep is a model of Polycystic Ovary Syndrome. Fibroblast Growth Factor 21 is an important metabolic hormone. Adolescent prenatally androgenized sheep have decreased Fibroblast Growth Factor 21. Their metabolic profile parallel studies on Fibroblast Growth Factor 21 deficiency. Targeting this hormone in adolescence may be a therapy in Polycystic Ovary Syndrome.